METHOD AND ETHICS OF STORY MAKING IN KOREAN LITERARY THERAPY - Cho , Eun-Sang; Im, Ji-Yeon (Journal of Dharma, 2019)
Examining the concept of literary therapy and its effects, this paper explores the method and unique ethical effects of ‘story making’ in Korean literary therapy, and proposes ’story making’ as a way for participating-readers to practice self-understanding and self-growth through Korean folktales. First, to lead storymaking to a literary therapy, we define the concepts of fictional narrative, self-story, folktales, participating-reader, literary therapist, and explain the role of these concepts. Second, we examine five stages involved in the process of story-making in Korean literary therapy: Understanding Participation-Reader and Folktale Selection, Making Fictional Narrative, Narrative Exploration, Connecting with Participant-Reader, Changing Story and Seeking Solutions. A participating-reader connects and integrates a literary text with his or her symptom via unique characteristics of each stage in step-by-step features. Third, the effects of literary therapy are practicing sustainable education through self-understanding and psychological growth and emulating the healthy lifestyles and ethics of others.